The efficacy and safety of direct-acting antiviral regimens for end-stage renal disease patients with HCV infection: a systematic review and network meta-analysis - Chen, Ruochan; Xiong, Yinghui; Zeng, Yanyang; Wang, Xiaolei; Xiao, Yinzong; Zheng, Yixiang (Frontiers in Public Health, 2023)
Background: HCV infection is an independent risk factor associated with adverse outcomes in patients with the end-stage renal disease (ESRD). Due to the wide variety of DAAs and the factor of renal insufficiency, careless selection of anti-hepatitis C treatment can lead to treatment failure and safety problem. The integrated evidence for optimized therapies for these patients is lacking. This study would conduct comparations of different DAAs, and facilitate clinical decision making.We conducted a systematic literature search in multiple databases (PubMed, Ovid, Embase, Cochrane library and Web of Science) up to August 07, 2023. Study data contained patient characteristics, study design, treatment regimens, intention-totreat SVR and AE data per regimen were extracted into a structured electronic database and analyses. The network meta-analysis of the estimation was performed by the Bayesian Markov Chain Monte Carlo methods.Results: Our search identified 5278 articles, removing the studies of duplicates and ineligible criteria, a total of 62 studies (comprising 4554 patients) were included. Overall, the analyses contained more than 2489 male, at least 202 patients with cirrhosis, and no less than 2377 patients under hemodialysis. Network meta-analyses of the DAAs in found receiving Ombitasvir (OBV) /Paritaprevir (PTV)/Ritonavir (R) plus Dasabuvir (DSV), Glecaprevir (G)/Pibrentasvir (P), and Sofosbuvir (SOF)/Ledipasvir (LDV) ranked as the top three efficacy for the HCV-infected ESRD patients. Stratified by genotype, the G/P would prioritize genotype 1 and 2 patients with 98.9%-100% SVR, the Sofosbuvir (SOF)/Daclatasvir (DCV) regimen had greatest SVR rates (98.7%; 95%CI, 93.0-100.0%) in genotype 3, the OBV/PTV/R regimen was the best choice for genotype 4, with highest SVR 98.1% (95%CI, 94.4-99.9%). In the pan-genotypic DAAs comparison, G/P regimen showed the best pooled SVR of 99.4% (95%CI, 98.6-100%). DAA regimens without Ribavirin (RBV) or SOF showed the lowest rates of AEs (49.9%; 95%CI, 38.4-61.5%) in HCV-infected ESRD patients.The G/P could be recommended as the best option for the treatment of pan-genotypic HCV-infected ESRD patients. The OBV/PTV/R plus DSV, SOF/ Velpatasvir (VEL), SOF/Ledipasvir (LDV) and SOF/DCV would be reliable alternatives for HCV treatment with comparable efficacy and safety profiles.